Effects of confluent language activities on the self-actualization and communicative competence of high school students - Cutiongco, Elene Cruz (Education quarterly.)
This study aims to investigate the effects of confluent language activities on the self-actualization and communicative competence of high school students as measured by their performance in Shostrom?s Personal Orientation Inventory (POI) in a teacher-made Communication Skills Test. The samples of the study were 30 second year high school students enrolled in U.P. Integrated School during School Year 1987-1988. The results of this study have important implications foe education in general and for language teaching in particular.